内陆苏打型盐碱化芦苇沼泽地苇-鱼-虾-蟹复合生态养殖的方法 (2016)
本发明提供了内陆苏打型盐碱化芦苇沼泽地苇-鱼-虾-蟹复合生态养殖的方法；包括蟹种驯化；鱼、虾、蟹苗种放养密度；养殖管理和捕捞；芦苇栽培。采用本发明的方法，蟹种的驯化存活率为81.3％；河蟹、鱼类和虾类的平均放养密度分别为2138只/hm、510尾/hm和11750尾/hm，平均捕捞重量分别为87.15kg/hm、233.30kg/hm和52.88kg/hm，平均捕捞规格分别为145.2g/只、670.6g/尾和5.3g/尾，平均回捕率分别为26.83％、69.45％和83.63％，芦苇的平均密度增加9.69％，平均产量提高12.47％，试验区的投入产出比为1∶3.174。 The invention provides a reed-fish-shrimp-crab ecological polyculture method for inland soda saline-alkaline reed swamps, which includes crab acclimation, stocking densities of fries, juvenile shrimps and juvenile crabs, culture management and catch and reed culture. After the method is adopted, the survival rate of acclimated crabs is 81.3 percent; the average stocking densities of river crabs, fishes and shrimps are 2138 river crabs/hm , 510 fishes/hm and 11750 shrimps/hm , the average catch weights of the river crabs, fishes and shrimps are 87.15kg/hm , 233.30kg/hm and 52.88kg/hm , the average catch specifications of the river crabs, fishes and shrimps are 145.2g per crab, 670.6g per fish and 5.3g per shrimp, the average